Emulating Upper Limb Disorder for Therapy Education. (18th November 2014) - Zakaria, Noor Ayuni binti Che; Komeda, Takashi; Yee Low, Cheng; Inoue, Kaoru
Robotics not only contributes to the invention of rehabilitation devices, it can also enhance the quality of medical education. In recent years, the use of patient simulators and part-task trainers in the medical education field has brought meaningful improvements in the training of medical practitioners. Nevertheless, in the context of therapy training for upper limb disorders, trainee therapists still have to engage directly with the patients to gain experience of the rehabilitation of physical diseases. In this work, a high-fidelity part-task trainer that is able to reproduce the stiffness of spasticity and rigidity symptoms of the upper limb, such as those observed in post-stroke patients and Parkinson's disease patients, has been developed. Based on the evaluation carried out by two experienced therapists, the developed part-task trainer is able to simulate different patient cases and help trainee therapists gain pre-clinical experience in a safe and intuitive learning environment.